The effects of sarcopenia on the prognosis of patients with acute-on-chronic liver failure: a systematic review and meta-analysis - Li, Wenyan; Deng, Rong; Luo, Yunting; Li, Hong; Chen, Fang; Zhao, Jing; Liu, Min; Liu, Qianxi; Mao, Yaojie; Zhang, Lixia (Frontiers in Nutrition, 2025)
ObjectivesSarcopenia is an important indicator affecting the prognosis of patients with end-stage liver disease. The purpose of this review is to systematically review all relevant studies to evaluate the impact of sarcopenia on the prognosis of patients with ACLF.MethodsWe systematically searched PubMed, Web of Science, Embase, the Cochrane Library, China Biomedical Literature Service System (CINAHL), China National Knowledge Infrastructure (CNKI), the WeiPu (VIP) and the Wanfang database for relevant articles published on or before August 1, 2024. Two independent reviewers conducted literature screening against predefined inclusion/exclusion criteria.ResultsThe systematic review included 12 cohort studies, with a total of 2,505 participants. Of these, 11 studies (2,072 participants) met the criteria for inclusion in the meta-analysis. The meta-analysis demonstrated that sarcopenia is significantly associated with an increased mortality risk in patients with ACLF [HR = 1.27, 95%CI (1.05, 1.54), p < 0.00001]. Subgroup analyses showed that the mortality risk was significantly increased in the subgroup of study with the outcome of short-term mortality [HR = 1.54, 95%CI (1.14, 2.08)], and prospective study [HR = 2.16, 95%CI (1.30, 3.60)].ConclusionThe meta-analysis of 11 studies (2,072 participants) revealed a significant association between sarcopenia and elevated mortality risk in ACLF patients. However, these findings should be interpreted with caution due to the limited number of included studies and higher heterogeneity in the analysis.Systematic review registrationCRD42023441039.